Of neighborhoods and boarding houses: popular spaces in classical Latin American cinema - Rodríguez Riva, Lucía (2026)
This article explores the peculiarities, similarities and differences in the imaginaries of the popular that consolidated Mexican and Argentine cinema during the classical period (between the 1930s and 1950s). Both cinematographies postulated mostly characters from the plebeian classes as protagonists of their fictions and, therefore, the environments inhabited by them become privileged scenarios to understand how models of sociability, coexistence and survival are configured. Thus, the neighborhoods (in Mexico) and the boarding houses (in Argentina) constitute two key environments to understand the representations of urban relations in contexts of economic modernization (due to the advance of industrialization) and political modernization (due to the incorporation of broad social sectors to the debate and participation in the public sphere). The presence of popular actors (such as Cantinflas and Germán Valdés “Tin Tan”, Luis Sandrini and Niní Marshall) is a kind of enclave, since they embodied the dislocations of those processes. This exploration is carried out from a comparative (Paranaguá) and cultural history perspective, framing the object of study in its respective cinematographic, historical and social contexts, based on the examination of a representative film corpus.